Functional analysis and its applications : proceedings of the International Conference on Functional Analysis and its Applications, dedicated to the 110th anniversary of Stefan Banach, May 28-31, 2002, Lviv, Ukraine - Kadets, V. M. (Vladimir M.); Zelazko, Wiesaw; Banach, Stefan, 1892-1945 (North-Holland mathematics studies, 2004)
The conference took place in Lviv, Ukraine and was dedicated to a famous Polish mathematician Stefan Banach { the most outstanding representative of the Lviv mathematical school. Banach spaces, introduced by Stefan Banach at the beginning of twentieth century, are familiar now to every mathematician. The book contains a short historical article and scientific contributions of the conference participants, mostly in the areas of functional analysis, general topology, operator theory and related topics.